2011
DOI: 10.1016/j.vaccine.2011.01.113
|View full text |Cite
|
Sign up to set email alerts
|

Ebola virus glycoprotein Fc fusion protein confers protection against lethal challenge in vaccinated mice

Abstract: Ebola virus is a Filoviridae that causes hemorrhagic fever in humans and induces high morbidity and mortality rates. Filoviruses are classified as "Category A bioterrorism agents", and currently there are no licensed therapeutics or vaccines to treat and prevent infection. The Filovirus glycoprotein (GP) is sufficient to protect individuals against infection, and several vaccines based on GP are under development including recombinant adenovirus, parainfluenza virus, Venezuelan equine encephalitis virus, vesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
74
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 49 publications
(63 reference statements)
0
74
1
Order By: Relevance
“…Given the positive association of serum neutralizing antibodies with survival against EBOV in human and animal model infections (9,34,38) and our observed correlation between survival and anti-EBOV GP antibody levels in sera from vaccinated mice, we evaluated the ability of sera from vaccinated mice to neutralize EBOV GP/VSVΔG pseudovirion infection of Vero cells, using the criterion of at least 50% inhibition of EBOV GP/VSVΔG infection as evidence of neutralization. Sera from mice vaccinated with even our highest concentrations of pseudovirions did not meet our criterion for neutralizing activity, despite providing robust protection against lethal challenge (Fig.…”
mentioning
confidence: 99%
“…Given the positive association of serum neutralizing antibodies with survival against EBOV in human and animal model infections (9,34,38) and our observed correlation between survival and anti-EBOV GP antibody levels in sera from vaccinated mice, we evaluated the ability of sera from vaccinated mice to neutralize EBOV GP/VSVΔG pseudovirion infection of Vero cells, using the criterion of at least 50% inhibition of EBOV GP/VSVΔG infection as evidence of neutralization. Sera from mice vaccinated with even our highest concentrations of pseudovirions did not meet our criterion for neutralizing activity, despite providing robust protection against lethal challenge (Fig.…”
mentioning
confidence: 99%
“…Therefore, immunization is considered to be essential in mitigating the high rate of mortality from viral hemorrhagic fevers. It was recently shown that Ebola virus glycoprotein can confer protection in vaccinated mice (26). Similarly, specific antibodies against CCHFV are protective in a suckling mouse animal model (6).…”
mentioning
confidence: 99%
“…The apparent size of this protein in polyacrylamide electrophoresis gel is 125-140 kDa due to heavy glycosylation [61,62]. The gp gene undergoes transcription by the L protein, involving furin cleavage and disulfide-bond formation between the N-terminus and the membrane proximal portion of GP [62][63][64]. This processing yields two peptide subunits required to synthesize the surface GP [60,65].…”
Section: Genome Organizationmentioning
confidence: 99%
“…This processing yields two peptide subunits required to synthesize the surface GP [60,65]. The membrane-anchored GP2 is covalently linked via disulfide bond to the N-terminus of GP1, which has a highly O-glycosylated mucinlike domain [63]. Upon infection, high amounts of GP1 is secreted from the cells after release from the GP2 subunit.…”
Section: Genome Organizationmentioning
confidence: 99%
See 1 more Smart Citation